Natural Polyphenols as Modulators of Etoposide Anti-Cancer Activity - Kluska, Magdalena (Int J Mol Sci, 2021)
Polyphenols are naturally occurring compounds found in abundance in fruits and vegetables. Their health-promoting properties and their use in the prevention and treatment of many human diseases, including cancer, have been known for years. Many anti-cancer drugs are derived from these natural compounds. Etoposide, which is a semi-synthetic derivative of podophyllotoxin, a non-alkaloid lignan isolated from the dried roots and rhizomes of Podophyllum peltatum or Podophyllum emodi (Berberidaceae), is an example of such a compound. In this review, we present data on the effects of polyphenols on the anti-cancer activity of etoposide in in vitro and in vivo studies.